The wealth of networks : how social production transforms markets and freedom - Benkler, Yochai (Yale University Press, 2006)
Production is shifting from physical products like blue jeans, to decentralized information goods, like articles on the Internet. This gives users more power (they can publish instead of just reading), creates more opportunities for democratic participation, lowers costs for developing countries, and democratizes the creation of our culture. This book analyzes these changes by looking at what new technologies make easy, applying an individualist economic model, and examining the effects on human beings. As the state's role has largely been to support big companies, this book will largely ignore it, even though it could be used as a force for good.